Perbedaan Efektivitas Metode PKM-RS dengan Diskusi dan Problem Solving dalam Peningkatan Pengetahuan dan Sikap dari Pasien DM Tipe II di RSUD Sunan Kalijaga Kabupaten Demak - Sukardjo, Sukardjo (Jurnal Promosi Kesehatan Indonesia, 2007)
Background : Diabettes mellitus (DM) disease needs to be well managed in order to obtain normal range of blood glucose level. If the patients could control their glucose level, they would have a better quality of life and prevent from other disease complications. Health education is very important action to improve awareness and attitudes of the diabetes patients in terms of how to manage their diabetes. The aim of this study is to identify the effectiveness between discussion and problem solving techniques in improving knowledge and attitudes of diabetes out-patients for managing their disease.Method : This study is a quasy experimental with three-group pretest-posttest design. Group one was treated using group discussion method and group two with problem solving technique. Whereas the other group as a control group. Each group contains 30 respondents.Result : The study shows that t-test value indicated the level of knowledge of patients in group one was lower than group two (t-test 5,726). However, the attitudes of patients in group two (2,472) also higher than group one (2,055). This study concludes that health education using problem solving was more effective than discussion technique to increase knowledge and attitudes of diabetes patients type II in Sunan Kalijaga Hospital Demak.Keywords:Health education, knowledge, attitudes, diabetes mellitus, discussion and problem solving tehnique.